Interaksi Sosial Pekerja Anak: Studi Kasus Anak yang Bekerja Sebagai Buruh Bangunan di RW.05 Desa Kalimukti Kabupaten Cirebon - Helmi, Muhammad; Siswono, Eko; Saipiatuddin, Saipiatuddin (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2019)
This research aims to: (1) Know the factors cause children to prefer working as builder rather than go to school. (2) Know the social interaction of child labourers in builder at the work environment (3) Knowing the changes lifestyle of child labourers after working as builder. This researched in RW.05 Kalimukti Village, Pabedilan District, Cirebon Regency more than three month since March to May 2019. The method used in this research is qualitative research methods, with data collection techniques through observation, interviews, Focus Group Discussion (FGD) and documentation. Data sources in this research are key informants and core informants consist of the chairperson of RW.05, head of a village 03, head of builder and parents of child laborers as key informants and four child laborers as builder as core informants. The results of research are conclude that (1) Factors underlying children who choose to work as builder rather than go to school are less of motivation to learn; Environment; Self-will (independent); Economic crush (2) There are forms of social interaction on child labourers in the form of cooperation, accommodation and obstacles in the form of conflicts that occur in child labourers in the work environment. As for the things that become barriers to child labor such as adaptation to the new environment (3) There is a change in lifestyle on the better habits in children after they are work as builder. As well as changes in the appearance and economic independence caused by the income received after work.